Service Quality, Experience and Customer Loyalty: Evidence of Willingness to Pay on the Jakarta Bandung High Speed Train - Arizal Ginartha; Ghufron Solikhul Amri; Muhammad Iqbal Firdaus; Haryono Haryono (Jurnal Ekonomi Manajemen Sistem Informasi, 2025)
The Jakarta-Bandung High-Speed Rail stretches over 142.3 km and offers First Class, Business Class, and Premium Economy options. To enhance its appeal and provide an unforgettable travel experience, the Jakarta-Bandung High-Speed Rail completes the journey between Jakarta and Bandung (or vice versa) in just 48 minutes, traveling at a speed of 350 km/h. However, the question arises whether the experience and services offered by this high-speed rail influence passengers' willingness to pay for their journey. This study aims to examine the impact of service quality, customer experience, and customer loyalty on passengers' willingness to pay. Data was collected through questionnaires distributed to 100 respondents who are customers of the Jakarta-Bandung High-Speed Rail. The survey assessed service quality, customer experience, and user loyalty using a Likert scale. This study utilized Partial Least Squares Structural Equation Modeling (PLS-SEM) for data analysis. The findings reveal a significant relationship between the variables studied, such as service quality positively impacting willingness to pay (WTP) and customer loyalty. Therefore, KCJB should focus on improving service quality and customer experience, developing loyalty programs, and running marketing campaigns that highlight the added value of their services.